Responses of Religion and Science to the Threats of the COVID-19 Pandemic in Indonesia: [Respon Agama dan Sains Terhadap Ancaman Pandemi COVID-19 di Indonesia] - Kurniawan, Wawan; Hudiyana, Joevarian; Muluk, Hamdi (Faculty of Psychology, Universitas Surabaya, 2022)
The COVID-19 pandemic has presented various responses in society. A number of individuals have believed in its existence and conducted health protocols properly, but there are also those who have done the opposite. During a pandemic, belief in science influences actions and responses in society. However, individuals often do not believe in scientific findings, such as the existence of the virus causing the COVID-19 pandemic (SARS-CoV-2). A number of previous studies have often assumed that science is in conflict with religion. But is religion truly the opposite of science? This article aims to look at the role of belief in science in Indonesian society, in responding to the COVID-19 pandemic, and is hoped to be read by various parties such as the general public, scientists, to policymakers. Furthermore, this article may help in understanding the position of science and religion under certain conditions, while also being able to examine the differences in responses that occur. In Indonesia, religion and science have not been at odds in responding to the COVID-19 pandemic. The two each have their respective roles in providing explanations of the problems that have occured. However, there are groups of religious fundamentalists and their perception in viewing science that require attention in further studies. Pandemi COVID-19 menghadirkan berbagai respon di masyarakat. Beberapa individu percaya akan keberadaannya dan melakukan protokol kesehatan dengan baik, akan tetapi ada pula yang melakukan hal sebaliknya. Pada masa pandemi, keyakinan terhadap sains (belief in science) memberi pengaruh pada tindakan serta tanggapan masyarakat. Akan tetapi, individu kerap tidak percaya dengan temuan ilmiah, seperti halnya tentang keberadaan virus penyebab pandemi COVID-19 (SARS-CoV-2). Sejumlah studi sebelumnya seringkali menganggap bahwa sains bertentangan dengan agama. Namun, apakah agama adalah faktor yang memang berkebalikan dengan sains? Artikel ini bertujuan untuk melihat peran belief in science pada masyarakat Indonesia dalam merespon pandemi COVID-19, dan diharapkan dapat dibaca oleh berbagai kalangan seperti masyarakat awam, ilmuwan, hingga pembuat kebijakan. Selain itu, artikel ini dapat membantu memahami posisi sains dan agama dalam kondisi tertentu, serta mampu menelaah perbedaan respon yang terjadi. Di Indonesia, agama dan sains tidak berseberangan dalam merespon kondisi pandemi COVID-19. Kedua hal tersebut memiliki perannya masing-masing dalam memberikan penjelasan atas permasalahan yang terjadi. Walaupun demikian, terdapat kelompok fundamentalisme agama dan persepsinya atas sains yang patut mendapat perhatian dalam studi selanjutnya.